Pengaruh Leverage, Likuiditas, Profitabilitas, Sales Growth, Good Corporate Governance dan Corporate Social Responsibility Terhadap Financial Distress Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Suryaningrum, Diah Hari; Adzroo, Naomi Ulayya (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study is to test, prove, and analyze the effect of leverage, liquidity, profitability, sales growth, good Corporate Governance, and Corporate Social Responsibility as independent variables that affect financial distress. This study uses secondary data in the form of financial statement data. The sample used was 310 financial statements of manufacturing companies listed on the Indonesia Stock Exchange during the period of 5 years 2015-2019, using the purposive sampling method. The analysis used in this research is logistic regression analysis. Based on the result of the study, it can be concluded that leverage, liquidity, profitability, and Corporate Social Responsibility have an effect on financial distress. Meanwhile, sales growth and Good Corporate Governance have no effect on financial distress.